Cancer Stem Cells in Moderately Differentiated Lip Squamous Cell Carcinoma Express Components of the Renin–Angiotensin System - Ram, Rachna S.; Brasch, Helen D.; Dunne, Jonathan C.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2017)
Aim We investigated the expression of the renin-angiotensin system (RAS) by cancer stem cells (CSC) subpopulations we have identified in moderately differentiated lip squamous cell carcinoma (MDLSCC). Method Ten MDLSCC samples underwent 3,3-diaminobenzidine (DAB) and immunofluorescent (IF) immunohistochemical (IHC) staining for (pro)renin) receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and receptor 2 (ATIIR2). NanoString analysis and Western blotting (WB) were performed on six MDLSCC samples for gene and protein expression, respectively. Results IHC staining showed PRR, ATIIR1 and ATIIR2 on cells within the tumor nests (TNs) and the stroma. ACE was localized to the microvessels within the stroma. WB detected PRR, ACE and ATIIR2. NanoString analysis confirmed expression of PRR, ACE and ATIIR1. Conclusion Components of the RAS: PRR, ATIIR1 and ATIIR2 are expressed on two CSC subpopulations in MDLSCC, one within the TNs and the other within the stroma. The endothelium of the microvessels within the stroma expresses ACE.